Mobile Application Development for Crisis Data. (2015) - Jain, Anubhav; Adebayo, Julius; de Leon, Eduardo; Li, Weihua; Kagal, Lalana; Meier, Patrick; Castillo, Carlos
Abstract: With the reactive nature of disaster relief efforts, the response time of NGO's and humanitarian organizations is critical. Organizations cannot predict the next crisis, nor can they build a catch all solution for any future problem. Consequently, the quicker a system is in place following a crisis, the more data can be collected to improve the relief efforts. Data is vital in assessing the severity of a crisis, informing organizations on how to prepare or give aid, and informing the community about an event. Mobile phones in general, and smartphones in particular, are an ideal tool for the collectionof this valuable data. The development effort required to create smartphone applications is usually substantial. There are technical barriers to entry, and usually lengthy development times. Because of this, traditional mobile application development has been limited in its ability to help disaster relief. The Punya framework, presented in this paper, drastically shortens the development time required for Android applications, while supporting the communication and sensor features needed to acquire data during a crisis scenario. Punya's advanced sensor functionality, as well as its data capture and reporting components, allow organizations to build mobile applications quickly that can gather both user and context data as well as visualize results.